The Environmental Risks Associated With the Development of Seaweed Farming in Europe - Prioritizing Key Knowledge Gaps - Campbell, Iona; Macleod, Adrian; Sahlmann, Christian; Neves, Luiza; Funderud, Jon; Øverland, Margareth; Hughes, Adam D.; Stanley, Michele (Frontiers in Marine Science, 2019)
Cultivation of kelp has been well established throughout Asia, and there is now growing interest in the cultivation of macroalgae in Europe to meet future resource needs. If this industry is to become established throughout Europe, then balancing the associated environmental risks with potential benefits will be necessary to ensure the carrying capacity of the receiving environments are not exceeded and conservation objects are not undermined. This is a systematic review of the ecosystem changes likely to be associated with a developing seaweed aquaculture industry. Monitoring recommendations are made by risk ranking environmental changes, highlighting the current knowledge gaps and providing research priorities to address them. Environmental changes of greatest concern were identified to include: facilitation of disease, alteration of population genetics and wider alterations to the local physiochemical environment. Current high levels of uncertainty surrounding the true extent of some environmental changes mean conservative risk rankings are given. Recommended monitoring options are discussed that aim to address uncertainty and facilitate informed decision-making. Whilst current small-scale cultivation projects are considered ‘low risk’, an expansion of the industry that includes ‘large-scale’ cultivation will necessitate a more complete understanding of the scale dependent changes in order to balance environmental risks with the benefits that seaweed cultivation projects can offer.